The H3+ ionosphere of Uranus: decades-long cooling and local-time morphology. (5th August 2019) - Melin, Henrik; Fletcher, L. N.; Stallard, T. S.; Miller, S.; Trafton, L. M.; Moore, L.; O'Donoghue, J.; Vervack, R. J.; Dello Russo, N.; Lamy, L.; Tao, C.; Chowdhury, M. N.
Abstract : The upper atmosphere of Uranus has been observed to be slowly cooling between 1993 and 2011. New analysis of near-infrared observations of emission from H3 + obtained between 2012 and 2018 reveals that this cooling trend has continued, showing that the upper atmosphere has cooled for 27 years, longer than the length of a nominal season of 21 years. The new observations have offered greater spatial resolution and higher sensitivity than previous ones, enabling the characterization of the H3 + intensity as a function of local time. These profiles peak between 13 and 15 h local time, later than models suggest. The NASA Infrared Telescope Facility iSHELL instrument also provides the detection of a bright H3 + signal on 16 October 2016, rotating into view from the dawn sector. This feature is consistent with an auroral signal, but is the only of its kind present in this comprehensive dataset. This article is part of a discussion meeting issue 'Advances in hydrogen molecular ions: H3 +, H5 + and beyond'.